CLIMATE CHANGE, FOOD INSECURITY, AND ADAPTIVE STRATEGIES IN SOUTHERN MADAGASCAR - Eric, Ralainirina Razokiny; Arrive, Tsitaire Jean; Emynorane, Ralaivao Hanginiaina (Journal of Development Economics and Digitalization, Tourism Economics, 2025)
Southern Madagascar has become a frontline of climate vulnerability, where recurring droughts, erratic rainfall, and land degradation have exacerbated chronic food insecurity. This qualitative study explores how climate change affects rural communities in the Androy and Anosy regions and investigates the local adaptive strategies developed in response to environmental and socio-economic stressors. Using an interpretive phenomenological approach, the study captures the lived experiences of affected populations through in-depth interviews and focus group discussions. A total of 24 informants were selected using purposive sampling, including smallholder farmers, female-headed households, local community leaders, NGO workers, and agricultural extension officers. Data were collected through semi-structured interviews, field observations, and document analysis of regional adaptation plans and NGO reports. The findings reveal that climate-induced food insecurity is not merely an ecological crisis but a deeply social issue influenced by poverty, gender roles, weak institutional support, and cultural land practices. Informants reported using a combination of traditional coping mechanisms such as food rationing, seasonal migration, and seed diversification and externally supported interventions such as cash-for-work programs and drought-resilient crops. However, many of these strategies remain short-term, reactive, and unequally accessible. This study concludes that while community resilience is evident, structural barriers persist in achieving long-term adaptation. Policy implications include the need for localized climate adaptation policies, strengthened agricultural extension services, and the inclusion of indigenous knowledge in planning processes. By centering voices from the most affected regions, this study contributes to a deeper understanding of the human dimensions of climate vulnerability in Madagascar.